The Effects of Obesity on Outcome in Preclinical Animal Models of Infection and Sepsis: A Systematic Review and Meta-Analysis - Wanying Xu; Dominique Pepper; Junfeng Sun; Judith Welsh; Xizhong Cui; Peter Q. Eichacker (Journal of Obesity)
Background. Clinical studies suggest obesity paradoxically increases survival during bacterial infection and sepsis but decreases it with influenza, but these studies are observational. By contrast, animal studies of obesity in infection can prospectively compare obese versus nonobese controls. We performed a systematic review and meta-analysis of animal investigations to further examine obesity’s survival effect in infection and sepsis. Methods. Databases were searched for studies comparing survival in obese versus nonobese animals following bacteria, lipopolysaccharide, or influenza virus challenges. Results. Twenty-one studies (761 obese and 603 control animals) met the inclusion criteria. Obesity reduced survival in 19 studies (11 significantly) and the odds ratio (95% CI) of survival (0.21(0.13, 0.35); I2 = 64%, p<0.01p < 0.01) but with high heterogeneity. Obesity reduced survival (1) consistently in both single-strain bacteria- and lipopolysaccharide-challenged studies (n = 6 studies, 0.21(0.13, 0.34); I2 = 31%, p=0.20 and n = 5, 0.22(0.13, 0.36); I2 = 0%, p=0.59, respectively), (2) not significantly with cecal ligation and puncture (n = 4, 0.72(0.08, 6.23); I2 = 75%, p<0.01), and (3) significantly with influenza but with high heterogeneity (n = 6, 0.12(0.04, 0.34); I2 = 73%, p<0.01). Obesity’s survival effects did not differ significantly comparing the four challenge types (p=0.49). Animal models did not include antimicrobials or glycemic control and study quality was low. Conclusions. Preclinical and clinical studies together emphasize the need for prospective studies in patients accurately assessing obesity’s impact on survival during severe infection.